Ghanaian radio and the Akan language: Unplanned language planning and development - Agyekum, K. (Issues in Political Discourse Analysis 3(3): 1-22, 2010)
This paper focuses on the sociolinguistic role of Ghanaian languages, especially Akan on the radio, with particular reference to linguistics, social issues, and the media. The study is based on Akan programmes on the radio, especially in Accra and Kumasi. It considers radio broadcasters and their audiences as agents of the development and modernisation of the Akan language. The paper provides a brief historical account of language use in education and the emergence of radio in Ghana. It argues that the media, especially radio, have chalked up success in their major role of educating, informing, and entertaining, through the use of Ghanaian languages. It points out that the Akan language has played a major role in bringing Ghanaian language into the media. We will emphasise that radio stations have developed language policies on two levels by determining what language(s) they use, and deciding on the content matter (style and register). These two policies have led to new usages and the propagation of new linguistic terminologies.
Keywords: Akan language; language policy; mass media; talk show; newspaper ideology